Strategic Priorities for Cultivating Commitment Amongst Academic Staff: The Militating Effect of Workplace Spirituality - Kokt, Desere; Palmer, Esther P. (SA Journal of Human Resource Management, 2019)
Orientation: Organisational commitment remains an ongoing concern for organisations, especially universities that often struggle to retain academic staff. Universities cannot operate or fulfil their mandate to society without the critical competencies of academic staff. Research purpose: This investigation focused on workplace spirituality as a militating factor in enhancing the commitment of academic staff. Motivation for the study: As organisational commitment remains a challenge for universities, this article contributes to a theoretical and empirical understanding of the militating influence of workplace spirituality. The study is underpinned by social learning theory and proposes strategic priorities to universities – informed by an empirical study conducted amongst academic staff members at a South African university. Research approach/design and method: The study employed a quantitative research approach and a structured questionnaire was administered to 285 academic staff members (ranging from junior lecturers to professors) of a South African university. The research design was a survey and, as a single university formed part of the study, regression analysis was used to establish the relationship between workplace spirituality and organisational commitment. Main findings: The empirical findings showed a strong linear relationship between workplace spirituality and organisational commitment. A regression formula was developed to statistically calculate the commitment score of individuals. Practical/managerial implications: The study proposed strategic priorities that may be useful to university management and human resource practitioners to cultivate increased commitment amongst academic staff. Contribution/value-add: The study contributed empirical evidence of the militating effect of workplace spirituality on organisational commitment, implying that workplace spirituality is a predictor for organisational commitment.